Mr Majeika and the Ghost Train - Carpenter, Humphrey; Rodgers, Frank (London Puffin Books., 1995)
When Class Three and Mr Majeika go to the Adventure Galaxy theme park, they certainly have an adventure, of the spooky kind. With real ghosts on the ghost-train ride, there's clearly something afoot